Optimization of Medium Components for Enhancing Antibacterial Activity of Marine Streptomyces aureofaciens A3 through Response Surface Methodology - Srikandace, Yoice; Kamarisima, Kamarisima; Putri, Sastia Prama; Aditiawati, Pingkan (Trends in Sciences, 2025)
This study is the first to report on the statistical optimization of an antibacterial production medium for the marine bacterium Streptomyces aureofaciens A3. Glycolic and furoic acids have not been previously documented as metabolites produced by Streptomyces, especially by S. aureofaciens A3. The antibacterial metabolites were generated in an ISP4 medium enriched with artificial seawater with different concentrations of starch, NaCl, and ammonium sulfate. Media components were optimized through the Response Surface Method (RSM) using the Box-Behnken design (BBD) in submerged fermentation. Antibacterial metabolites produced during fermentation were extracted with ethyl acetate (EA) to obtain EA extracts. The extract activities were tested using the Kirby-Bauer method, and the extract compounds were annotated using GC/MS. The results showed that the specific concentrations of starch, ammonium sulfate, and NaCl enhanced the antibacterial activity for each tested bacteria were 11.06 - 12.07 g/L for starch and 1.39 - 1.56 g/L for ammonium sulfate and 1.76 - 2.45 g/L for NaCl. The media increased higher antibacterial activity against pathogens with rising percentages of inhibition zones of E. coli (62.33 %), S. aureus (9.41 %), S. typhimurium (48.69 %), P. aeruginosa (39.16 %) and B. subtilis (8.58 %), respectively. The inhibition zones of each test bacteria were 10.88 - 17.97 mm and categorized as strong antibacterial activity. GC/MS derivatization results showed that the annotated compounds in EA extracts consisted of primary metabolites such as glycolic acid, palmitic acid, stearic acid, lauric acid, myristic acid, oleic acid and secondary metabolites were furoic acid, phthalate acid, benzoic acid, methylmalonic acid. This study showed that the RSM method is efficient and effective for improving the activity of broad-spectrum antibacterial agents produced by S. aureofaciens A3. The application of RSM to optimize ISP4 medium enables the large-scale production of antibacterial metabolites for the pharmaceutical industry. HIGHLIGHTS The antibacterial activity of marine Streptomyces aureofaciens A3 was first optimized using the Response Surface Method with ISP4-modified media. Broad-spectrum antibacterial activity increases against all pathogenic bacteria with a media composition similar to seawater. The low ammonium sulfate concentration induces higher antibacterial activity against bacterial pathogens. GRAPHICAL ABSTRACT